Presidency of the Republic's Documentation and Information Centre, Lisbon. Portugal - Sequeira, Marta (TC Cuadernos, 2022)
The premises of the Centre of Documentation and Information of the Presidency of the Republic, housed since 1982 in the basement of the Annex building of the National Palace of Belém – the official residence of the Head of State of Portugal. proved to be, in 1997, inadequate for the growing work of supporting the Civil and Military Houses. The General Secretariat of the Presidency of the Republic then promoted a consultation for the design of a new building, located in the garden area. Unlike the other proposals submitted to tender, which implied a reduction of the plant area, Carrilho da Graça's project promoted, on the contrary and surprisingly, the preservation of almost all its surface. The palace's Renaissance Garden had been sculpted in terraces along the hillside since the 16th century. The intervention area defined for the new building consisted, however, of a portion of non-squated land, located to the north of the palace. The analysis of its topography, namely the recognition of its highest point, to the west – at approximately the same level as the Cascade Garden and the pavement of the main building's main floor and its lowest, to the east – with a level some six metres lower, approximately the same as the Patio das Damas – suggested the creation of a platform that, giving continuity to the garden, contains the programme below, opening it up to the east. This strategy is similar to the one adopted by João da Silva Telo de Menezes when, inspired by the ménagerie royale at Versailles, he built the cages that were to be occupied by wild animals, set into the supporting wall under the parterre to the west of the main core of the palace.